Ecological Impact on Stingless Bees: Evaluating Pollen Load and Body Size Post-Introduction - Suhri, Andi Gita Maulidyah Indraswari; Kahono, Sih; Riendriasari, Septiantina Dyah; Syahribulan; Salatnaya, Hearty; Rahmah, Mufti Hatur (HAYATI Journal of Biosciences, 2025)
Changes in foraging behavior of stingless bees are caused by their introduction to new environments with varying biotic and abiotic factors. These bees struggle to adapt due to the shift from their original range. Biotic factors, particularly food source abundance, are crucial for their survival. Limited resources and reduced competition can decrease hive pollen, affecting larval nutrition and adult morphological growth. This study examines the physical effects of introducing stingless bees from Sulawesi to Jawa, Indonesia, using PCA to analyze 35 morphological traits and a haemocytometer to calculate pollen load. Morphometry was performed on ten separate colonies and ten different individual worker bees. Research findings indicate that the most significant size changes were observed in the forewing and hindwing lengths of worker bees at the introduction site. The smaller body size in the new environment indicates less available food in the nest. The lower pollen collection in the new environment compared to their natural habitat confirms this. The decline in pollen load is attributed to biotic factors like competition and food availability. When stingless bees become non-native, they face competition with existing species, including natives. Abiotic factors do not significantly influence the reduction in worker bees' foraging activity in the new environment. Changes in environmental factors significantly influenced the morphometric measurements of worker bees, following their introduction to lowland areas.